The Importance Of Legal Basis For The Imposition Of International Economic Sanctions In The Security Council - رجب, هيا; رامي كاسر لايقه; ماهر صالح الليوا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the foundations on which the security council builds its decisions and to delve into them in the event of a threat to international peace and security، in addition to evaluating the international economic sanctions approved by the security council and the individual measures imposed by one of the major countries، to this end، the researcher has collected private information about the security council since the founding of the United Nations following the collapse of the League of Nations، with resorting to the analysis of the legal basis on which the signing of the international economic sanctions that were stipulated in Chapter VII of the charter of the United Nations was based to reach the extent of independence of international economic sanctions that are applied against countries that violate the provisions and rules of international law. This study reached a number of results، the most important of which are: The resolutions of the Security Council، despite the fact that the Charter of the United Nations has given it broad powers in its primary task of maintaining international peace and security، it may be confused and bias in favor of major countries and foremost United States of America.